(untitled) (Lundiana: International Journal of Biodiversity, 2006)
Cladistic analysis of external morphology and skeletal characters was undertaken for 37 species of Apteronotidae, Neotropical electric fishes. Orthosternarchus + Sternarchorhamphus (included here in Sternarchorhamphinae status novo) are proposed to be the sister taxa to all remaining apteronotids, most of which form a basal polytomy in Apteronotinae. Several apteronotid species are currently incertae sedis but the monophyly of several genera were corroborated. Sternarchorhynchus is proposed to be the sister group of Ubidia magdalensis + Platyurosternarchus macrostomus, together forming the Sternarchorhynchini. Snout elongation was revealed to have occurred in several independent evolutionary lines as the Sternarchorhynchini, Orthosternarchus and Sternarchorhamphus. Apteronotus is restricted here to A. albifrons + A. jurubidae and postulated to be the sister group to Parapteronotus, which includes P. hasemani + P. macrostomus. “Apteronotus” leptorhynchus is postulated to be the sister group to “Apteronotus” cuchillo + Sternarchogiton cuchillejo and this three-species group is itself postulated to be the sister group of Apteronotus + Parapteronotus, and “Apteronotus” bonapartii postulated to be the sister group to “Apteronotus” apurensis. Autapomorphies were found for most of the species. A classification is presented for the family.